The moral interpretation of religion - Byrne, Peter, 1950- (Reason and religion (Edinburgh, Scotland), 1998)
"An analysis of some of Kant's key writings is offered as a viable way of constructing religion's key features and the structure of moral interpretation. Added to this, the book explores the work of several contemporary authors. It includes a detailed exposition and discussion of Iris Murdoch's account of morality and its relation to religion. This discussion leads on to an analysis of Wittgensteinian perspectives in the contemporary philosophy of religion."--Jacket.